The Dilemma of the European Integration Principle—Ensuring Energy Independence of the European Union - Litră Adriana Veronica; Nichifor Eliza; Chițu Ioana Bianca; Zamfirache Alexandra; Brătucu Gabriel (Sustainability, 2023)
The European Union’s energy policy confronts the intricate challenge of achieving energy independence through integration and transition, necessitating a careful calibration of its implementation scale. Recognizing that the heightened energy dependence represents a threat to the economic convergence and cohesion of the member states, the authors adopted a comprehensive approach to scrutinizing the energy landscape. The study examines the orientation toward renewable energy sources, encompassing their utilization in both transportation and household electricity supply. Leveraging a combination of statistical and econometric methodologies, the researchers analyzed the EU’s energy composition, evaluating its far-reaching impact on both micro- and macroeconomic dimensions. Beginning with the central endogenous variable of the study, dependence on imports, the research extends to the assessment of gross available energy. Through rigorous examination, the authors underscored the pivotal role of renewable fuels in final energy consumption and demonstrated the influence of green energy sources on household consumption. This investigation, complemented by the section of the ARIMA model for electricity price modeling, not only elucidated the dilemma but also presented renewable energy sources as a viable solution to curtail the European Union’s dependence on energy imports, even in their current underutilized state.
This article was originally published in Sustainability (MDPI) and is licensed under a Creative Commons Attribution (CC BY) 4.0 International License. This license permits use, sharing, distribution, and reproduction in any medium or format, provided appropriate credit is given to the original authors and source, a link to the license is included, and any changes are indicated. The article is available at: https://www.mdpi.com/2071-1050/15/21/15560 To view a copy of this license, visit: http://creativecommons.org/licenses/by/4.0/